Teaching on-Topic Conversational Responses to Students with Autism Spectrum Disorders Using an iPad App. Issue 2 (4th March 2022) - Sng, Cheong Ying; Carter, Mark; Stephenson, Jennifer
ABSTRACT: Difficulties with social conversation can be a direct result of the social skills deficit in individuals with autism spectrum disorders (ASD). The popularity of hand-held devices and the development of commercial apps has expanded the scope of teaching social skills via this modality. This study extends an earlier pilot study in which a participant was successfully taught to increase on-topic conversational responses. A multiple probe across participants design was used to test if a commercially available app could be used to teach simple on-topic conversational responses and if any learnt skills would generalise to different contexts. The participants in this study all performed differently in response to the intervention and the reasons for the variability in results are discussed.